Krishna
0

Step 1: Consider a right angle triangle

             NOTE: Right angle triangle ABC with right angle is at B


                


Step 2: Write the Pythagoras theorem to the triangle.

             NOTE: Take the angle A

                           (hypotenuse)^2 = (opposite)^2 + (adjacent)^2

                                 AC^2 = BC^2 + AB^2


Step 3: Dividing each term by opposite side.(BC) and simplify


                  EXAMPLE: \frac{AC^2}{BC^2} = \frac{AB^2}{BC^2} + \frac{BC^2}{BC^2}

                                     (\frac{AC}{BC})^2 = (\frac{AB}{BC})^2 + (\frac{BC}{BC})^2


                                   (\frac{hypotenuse}{opposite})^2 = (\frac{adjacent}{opposite})^2 + 1^2


                                   (\cosec A)^2 = (\cot A)^2 + 1


                                     1 + \cot^2 A = \cosec^2 A